Predictors of Premature Rupture of Membranes among Pregnant Women in Rural Uganda: A Cross-Sectional Study at a Tertiary Teaching Hospital - Byonanuwe, Simon; Nzabandora, Emmanuel; Nyongozi, Baltazar; Pius, Theophilus; Ayebare, David Santson; Atuheire, Collins; Mugizi, Wilson; Nduwimana, Martin; Okello, Maxwell; Fajardo, Yarine; Ssebuufu, Robinson (International Journal of Reproductive Medicine, 2020)
Background. Premature rupture of membranes (PROM) is a common condition in developed and developing countries and poses a serious threat to the maternal and fetal well-being if not properly managed. This study delineated the prevalence and predictors of PROM in the western part of Uganda so as to guide specific preventive measures. Methods. A cross-sectional study design was conducted in the months of September 2019 to November 2019. A total of 334 pregnant women above 28 weeks of gestation admitted at the maternity ward of KIU-TH were consecutively enrolled. Interviewer-administered questionnaires were used to obtain the data. Descriptive statistics followed by binary logistic regression were conducted. All data analyses were conducted using STATA 14.2. Results. Of the 334 pregnant women enrolled, the prevalence of PROM was found to be 13.8%. The significant independent predictors associated with lower odds of PROM were no history of urinary tract infection (UTI) in the month preceding enrollment into the study (aOR=0.5, 95% CI: 0.22-0.69, p=0.038) and gestational age of 37 weeks or more (aOR=0.3, 95% CI: 0.14-0.71, p=0.01) while history of 3 or more abortions (aOR=13.1, 95% CI: 1.12-153.62, p=0.05) was associated with higher likelihood of PROM. Conclusions. Majorly urinary tract infections, low gestational age, and abortions influence premature rupture of membranes among women. There is a great need for continuous screening and prompt treatment of pregnant women for UTI especially those with history of 3 or more abortions at less than 34 weeks of gestation.